1979
DOI: 10.1111/j.1471-0307.1979.tb01901.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of some manufacturing conditions on the development of flavour in Cheddar cheese

Abstract: Organoleptic assessments by the NIRD panel of Cheddar cheeses made with Streptococcus cremoris NCDO 924 or 1986, either in enclosed vats excluding nonstarter flora or in open vats, showed that high viable starter populations in curd did not give stronger‐flavoured cheese, but led to the development of bitterness. Cheeses made in open vats developed typical flavour more rapidly than those made in enclosed vats. Maturation temperature was the most important factor in determining the flavour intensity; cheese rip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
3
15
0
4
Order By: Relevance
“…In agreement with others, (Law, Hosking, & Chapman, 1979;Cromie, Giles, & Dulley, 1987;Martley & Crow, 1993;Folkertsma, Fox, & McSweeney, 1996) ripening temperature had a significant effect on NSLAB populations (Fig. 1).…”
Section: Microbiological Analysissupporting
confidence: 93%
“…In agreement with others, (Law, Hosking, & Chapman, 1979;Cromie, Giles, & Dulley, 1987;Martley & Crow, 1993;Folkertsma, Fox, & McSweeney, 1996) ripening temperature had a significant effect on NSLAB populations (Fig. 1).…”
Section: Microbiological Analysissupporting
confidence: 93%
“…As reported by Law et al (1979), maturation temperature was the most important factor in determining the flavour intensity of Cheddar cheese made with Lactococcus lactis subsp cremoris NCDO 924 or 1986, either in enclosed (excluding non-starter flora) or open vats. Cheeses ripened at 13 oC for 6 months developed a stronger flavour with less bitterness than those ripened at 6 oC for 9 rnonths, irrespective of the starter or vat used.…”
Section: Ripening Temperaturementioning
confidence: 59%
“…Law et al (1979) found that starter numbers decreased more slowly in cheese ripened at 8 than at 13°C while Cromie et al (1987) reported that starter counts were lower in chee se stored at 8 "C th an at 15, 17.5 or 20 oc. NSLAB numbers in cheeses ripened at 4 "C were quite low even after 6 months and increasing the ripening temperature resulted in increased numbers of NSLAB.…”
Section: Discussionmentioning
confidence: 99%